2013
DOI: 10.1039/c2cp44352j
|View full text |Cite
|
Sign up to set email alerts
|

A new hematite photoanode doping strategy for solar water splitting: oxygen vacancy generation

Abstract: The enhancement of the electrical conductivity by doping is important in hematite (α-Fe(2)O(3)) photoanodes for efficient solar water oxidation. However, in spite of many successful demonstrations using extrinsic dopants, such as Sn, Ti, and Si, the achieved photocurrent is still lower than the practical requirement. There is still lack of our understanding of how intrinsic oxygen defects can change the photocurrent and interact with the extrinsic dopants. In this study, we systematically investigate the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 29 publications
4
93
0
Order By: Relevance
“…31,34,35,42 Additional information about the phase of the nanostructures forming the sample top surface is obtained using X-ray diffraction (XRD) patterns performed with a grazing incidence angle of 0.5°. The XRD spectra presented in Figure 2 (a) show that all samples contain hematite, magnetite, and iron, a result consistent with the mixed iron oxides formed during thermal oxidization of iron foils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…31,34,35,42 Additional information about the phase of the nanostructures forming the sample top surface is obtained using X-ray diffraction (XRD) patterns performed with a grazing incidence angle of 0.5°. The XRD spectra presented in Figure 2 (a) show that all samples contain hematite, magnetite, and iron, a result consistent with the mixed iron oxides formed during thermal oxidization of iron foils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This oxygen‐deficient thermal decomposition method has further been extended to a two‐step low temperature (350 °C) activation process . More importantly, by coupling the inducing oxygen vacancy and element‐doping (such as Sn, and Ti), the photoactivity of hematite nanostructure was further increased. In spite of the recent progress toward enhancing the photocurrent density, an outstanding challenge for hematite photoanode is the large onset voltage, due to the slow water oxidation kinetics and low lying conduction band .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al recently demonstrated the intentional introduction of oxygen vacancies within the crystal structure of hematite thin films through controlled annealing under an oxygen-deficient atmosphere. [15] As the partial pressure of oxygen was decreased during the annealing step, the photocurrent response was found to increase concurrently. This was correlated to a higher number of Fe 2 + sites resulting from an increase in the number of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 97%